Breast cancer prevention behaviour of nurses and midwives - introduction to the discussion - Marianna Charzyńska-Gula; Grażyna Rożek; Piotr Szulich; Agnieszka Sojda; Bogdan Tomczyk; Marta Zielinska (Kazimierz Wielki University, 2024)
Introduction Nurses and midwives are a large and therefore very important - for the population effect of many public health activities - group of health care professionals. Breast cancer prevention is one of them. Aim of the study The aim of the study was to initiate a discussion on the decision-making processes related to the reporting of breast cancer screening by nurses and midwives. The discussion was prompted by the diagnosis of analogous behaviours in a selected group of nurses and midwives working in a selected hospital. Material and methods A total of 118 nurses and midwives working in one of the Podkarpackie hospitals were studied. A diagnostic survey was used with an author's questionnaire prepared for this study with elements of a knowledge test. The study was conducted in January 2023. Results In the group of nurses and midwives aged 50 years and older, 10% of nurses and 33.3% of midwives had never performed mammography. Breast ultrasound had never been performed by 25% of nurses and 23.8% of midwives. The reasons for this are varied and stem from both the family experience of the respondents and personal health concerns and beliefs. In the light of the review, it was shown that the participation of nurses and midwives in breast cancer prevention programmes requires a special approach in the design of such programmes and the attitude of nurses and midwives towards participation in oncology screenings demonstrates the need for special support for this group in their decisions. Conclusions There is an urgent need to use different approaches and models in the preparation of modern decision aids for women recipients of oncology prevention programmes that take into account the trade-offs and preferences of women from both groups - medical women and their clients.